Contribution to the knowledge of Lactuca L. (Asteraceae) in the United Arab Emirates - Sakkir, Sabitha; Güzel, Murat Erdem; Al Mansouri, Maitha; Soora, Pritpal (Biodiversity: Research and Conservation, 2023)
We present new data on the distribution of Lactuca species and review the currently documented data on the genus in the United Arab Emirates (UAE). L. serriola L. is recorded for the first time from Abu Dhabi Emirate. L. dissecta D. Don, L. serriola, and L. orientalis (Boiss.) Boiss. were already reported from other emirates. Detailed morphological descriptions, types, distribution maps, and a key to Lactuca species in the UAE are included. We also highlight the deficiency of the documentation with herbarium specimens in the UAE.